Integration of Remote Sensing and GIS Technologies for Blue Carbon Ecosystem Monitoring in Lakkang Island, Makassar City - Nyompa, Sukri; Haris, Haris; Amalul, Muhammad Arib Musba; Albatuul, Fatimah (Tunas Geografi, 2023)
Blue carbon ecosystem has a very important role in maintaining the quality of environments. Form of monitoring processes is needed to be able to provide direction for decision making, related to its management planning. Remote sensing technologies that is integrated with Geographic Information Systems (GIS) is a form of monitoring methods that can be carried out more quickly, easily and accurately. Lakkang Island in Makassar City has a blue carbon ecosystem in form of mangroves, that have very important role in absorbing carbon emissions. This research was conducted with the aim of integrating remote sensing and GIS technologies in monitoring blue carbon ecosystems.  Monitoring processes focused on distribution and extentions of the blue carbon ecosystem which is carried out through a random forest algorithm. Monitoring of the physical condition like density levels of the blue carbon ecosystem is carried trough the NDVI analysis. The results showed that the distribution of the blue carbon ecosystem on Lakkang Island tends to follow the main flow of the Tallo River, with an area of 58.29 hectare. Physical conditions of the blue carbon ecosystem is dominated by dense mangroves that reaching 46% from total area of the ecosystem.Keywords: Blue Carbon, Ecosystem Monitoring, Lakkang